Principles of structural design wood, steel, and concrete - Gupta, Ram S. (CRC Press, 2014)
"Anyone involved with structural design must maintain a functional understanding of wood, steel, and concrete design principles. Covering all of these materials, this book provides a self-contained authoritative source that elaborates on the most recent practices together with the code-connected fundamentals that other books often take for granted. Organized for ready reference, the text presents the LRFD approach for designing structural elements according to the latest codes. Written primarily for architecture and construction management students, it is equally suitable for those in civil and structural engineering programs"